A new acorane sesquiterpenes of Lysionotus pauciflorus maxim. Form Guizhou province, China. (December 2020) - Zhang, Jiayu; Yi, Ping; Xiong, Yan; Du, Caixia; Zhang, Yu; Yuan, Chunmao; Huang, Liejun; Gu, Wei; Hao, Xiaojiang
Abstract: A new acorane sesquiterpene (1 ), together with fourteen known compounds were isolated from the whole plant of Lysionotus pauciflorus Maxim. The chemical structures of the compounds were identified by physio-chemical properties and 1D-NMR, 2D-NMR, ESI-MS, IR and ECD spectra. Among them, six compounds (1, 4, 6, 7, 13, 15 ) were first found in the genus Lysionotus . The chemotaxonomic significance of the isolated compounds in the genus Lysionotus and family Gesneriaceae were discussed. Highlights: A phytochemical investigation of the Lysionotus pauciflorus Maxim. has been finished. A new acorane sesquiterpene was isolated from the whole plant of L. pauciflorus. Six known compounds were reported from the genus Lysionotus for the first time. The chemotaxonomic significance of compounds and L. pauciflorus were discussed.